Employee engagement as a predictor of organizational commitment amongst Cottco employees, head office, Harare - Mirazi, Abigail Singatia (Midlands State University, 2017)
Employee engagement is a concept that is being adopted globally by many organizations because it renders competitive advantage through human capital. This study was mainly focused on employee engagement as a predictor of organizational commitment amongst Cottco employees, Head Office, Harare. The chief aim of this study was to assess the degree to which employee engagement can impact upon the three components of organizational commitment, that is, affective commitment, continuance commitment, normative commitment and organizational commit as a whole. This study adopted the quantitative research approach particularly the correlational design. This prompted the use of questionnaires; in this case, standardized instruments were used. The Gallup Worker Audit by Gallup was used to gauge employee engagement. The Organizational Commitment Questionnaire by Allen and Meyer was used to measure organizational commitment. Fifty five employees, managerial and non managerial staff, participated in the study. The outcomes of the research revealed the levels of engagement within Cottco at critical lows, because only 36.4% represents employees with high levels of engagement while the remaining 63.6 % have low levels of engagement. The findings also indicated that employee engagement can indeed act as a predictor of organizational commitment r =0.799; p< 0.01 which is a positive, significant relationship. Employee engagement also had significant positive relationships with normative, continuance and affective commitment where r= 0.812, p<0.01; r= 0.399, p< 0.03; r= 0.799, p<0.01 respectively. The lows levels at Cottco need to be addressed in order to retain its employees and achieve organizational success.